Immunoreactivity of Gluten-Sensitized Sera Toward Wheat, Rice, Corn, and Amaranth Flour Proteins Treated With Microbial Transglutaminase - Scarnato, Lucilla; Gadermaier, Gabriele; Volta, Umberto; De Giorgio, Roberto; Caio, Giacomo; Lanciotti, Rosalba; Del Duca, Stefano (Frontiers in Microbiology, 2019)
The aim of this study was to analyze the effects of microbial transglutaminase (mTG) on immunoreactivity of wheat and gluten-free cereals flours’ towards sera of patients with celiac disease (CD) and non-celiac gluten sensitivity (NCGS). Both doughs and sourdoughs, the latter prepared by a two-step fermentation with Lactobacillus sanfranciscensis and Candida milleri, were studied. In order to evaluate the IgG-binding capacity towards the proteins of the studied flours, total protein as well as protein fractions enriched in albumins/globulins, prolamins and glutelins, were analyzed by SDS-PAGE and enzyme-linked immunosorbent assay (ELISA). Results showed that while mTG modified both gluten and gluten-free flour by increasing the amount of cross-linked proteins, it did not affect serum’s immune-recognition. In fact, no significant differences were observed in the immunoreactivity of sera from CD and NCGS patient’ towards wheat and gluten free protein extracts after enzyme treatment, nor did this biotechnological treatment affect the immunoreactivity of control samples, the sera of healthy patients’. These results suggest that mTG may be used as a tool to create innovative gluten and gluten-free products with improved structural properties, without increasing the immune-reactivity towards proteins present either in doughs or in sourdoughs